Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00417-013-2364-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of lamellar macular hole secondary to epiretinal membrane

Abstract: In LMH secondary to ERM with significant visual decrease, ERM and ILM peeling may improve BCVA. Postoperative gas tamponade is associated with better restoration of macular configuration. Final BCVA is related to an intact photoreceptor IS-OS junction rather than to the normalization of the macular contour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 17 publications
2
51
0
4
Order By: Relevance
“…This finding is important in light of the fact that recommendations for surgical repair of eyes with LMHs are controversial, with some authors reporting good surgical outcomes and others documenting worsening of anatomic features and VA after surgery. 1,3,7,10,11,[21][22][23] The limitations of this study include its retrospective nature, the relatively restricted number of patients, and the variable duration of follow-up.…”
Section: In This Retrospective Study We Show That In Eyesmentioning
confidence: 99%
“…This finding is important in light of the fact that recommendations for surgical repair of eyes with LMHs are controversial, with some authors reporting good surgical outcomes and others documenting worsening of anatomic features and VA after surgery. 1,3,7,10,11,[21][22][23] The limitations of this study include its retrospective nature, the relatively restricted number of patients, and the variable duration of follow-up.…”
Section: In This Retrospective Study We Show That In Eyesmentioning
confidence: 99%
“…Anatomically, most of the patients (92%) had an improvement of the LH contour with reduction of IRF. Not a single patient had disruption of the inner segment-outer segment junction, which is more important for the final vision rather than normalization of the macular contour [17,20]. With respect to the short-term follow-up, we expect further BCVA increase in the long term.…”
Section: Discussionmentioning
confidence: 92%
“…Surgical treatment of LHEP remains controversial as various studies have shown different outcomes [8][9][10][11][12][13][14][15][16][17]. In addition, many vitreoretinal surgeons hesitate to perform vitrectomy because of the fear to induce an iatrogenic macular hole or defects in the inner segment-outer segment junction [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations